2005
DOI: 10.1111/j.1540-8191.2005.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin Decreases Ischemic Damage During Coronary Revascularization

Abstract: Aprotinin limits ischemic injury during acute coronary revascularization by decreasing ventricular arrhythmias and lung edema, preserving endothelial function, and minimizing myocardial necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The cardioprotection exerted by aprotinin in this study was characterized by a 50% reduction in necrotic myocardium and by a marked attenuation of plasma CK activity compared to treatment with vehicle alone. These findings are in keeping with previous data from a number of animal models ( Pruefer et al , 2002 ; Khan et al , 2004 ; Lazar et al , 2005 ). Our data are novel in that they demonstrate cardioprotection using parallel techniques and these show that firstly, the effects of aprotinin are dose‐dependent (with no significant effect using ‘low‐dose’ aprotinin) and, secondly, that aprotinin is effective when given at the end of the ischaemic period (thus, indicating an effect on reperfusion injury).…”
Section: Discussionsupporting
confidence: 91%
“…The cardioprotection exerted by aprotinin in this study was characterized by a 50% reduction in necrotic myocardium and by a marked attenuation of plasma CK activity compared to treatment with vehicle alone. These findings are in keeping with previous data from a number of animal models ( Pruefer et al , 2002 ; Khan et al , 2004 ; Lazar et al , 2005 ). Our data are novel in that they demonstrate cardioprotection using parallel techniques and these show that firstly, the effects of aprotinin are dose‐dependent (with no significant effect using ‘low‐dose’ aprotinin) and, secondly, that aprotinin is effective when given at the end of the ischaemic period (thus, indicating an effect on reperfusion injury).…”
Section: Discussionsupporting
confidence: 91%
“…Aprotinin is a naturally occurring broad spectrum protease inhibitor obtained from bovine lung. Notwithstanding recent debate over its use sparked by 2 recent articles reporting an association with renal failure and other complications, 2,3 aprotinin has found widespread use in cardiac surgery for its benefits in reducing perioperative bleeding, 4 myocardial ischemia, 5 and cerebral events. 6 Animal studies have revealed a variety of effects including cardioprotection, reduced endothelial dysfunction and leukocyte migration.…”
mentioning
confidence: 99%
“…Aprotinin is suggested to reduce capillary leakage and is of interest as it is already used in cardiac surgery to inhibit hyperfibrinolysis. In patients undergoing cardiac surgery, aprotinin is thought to decrease pulmonary edema [30]. In experimental CPB, aprotinin reduced myocardial edema and fluid requirements [31].…”
Section: Discussionmentioning
confidence: 99%